Perbandingan Pola Jamkesmas dan JKN dalam Pelayanan Kesehatan Masyarakat: Studi pada Puskesmas Se-Kabupaten Pangandaran - Dede Ahmad Saefulloh; Enas Enas (International Forum of Researchers and Lecturers, 2024)
This research is motivated by several problems that: There are several things that have been identified in relation to the implementation of the national health insurance policy on public health services, such as: In supporting the success of health services and reducing health costs for the community, the government in collaboration with PT. Health Insurance holds a Community Health Insurance (Jamkesmas) program. Social Health Insurance services include first-level outpatient care, advanced outpatient care, inpatient care, drug services, childbirth, advanced diagnostic support services, medical equipment and supplement services, operative and non-operative medical procedures, medical rehabilitation services, intensive care Intensive Care Unit (ICU), hemodialysis (dialysis), and emergency services. The method used is a qualitative descriptive method. The results of the study show that: Based on the results of the analysis, it is known that in the service process, both the Jamkesmas pattern and the JKN pattern, are carried out in accordance with the service procedures, namely: self-esteem, meeting expectations (exceed expectations), improvement and rediscovery, forward-looking (vision), continuous improvement (improving), full attention (care, empathy), finally always holding empowerment (empowerment). The obstacles faced by employees in implementing the Jamkesmas and JKN patterns in public health services in Pangandaran Regency are: (1) access to health center services is still limited to certain diseases; (2) the availability of expert personnel is still minimal, (3) the availability of nurses is still limited; (4) the availability of other professional personnel such as pharmacists is still lacking; (5) inpatient facilities are still lacking and so on, which results in less than optimal service. Efforts made by employees in overcoming obstacles when implementing the Jamkesmas and JKN patterns in public health services in Pangandaran Regency are (1) improving access to health center services; (2) adding expert personnel, (3) adding nurses; (4) adding professional personnel; (5) improving inpatient facilities.